An Intelligent Model for Co-Extraction of Opinion Words and Targets from Online Reviews Using Expectation Maximization - Priya , N. Shanmuga; Nanthini , R.; Padmanatharathinam , R. (International Journal of Membrane Science and Technology, 2023)
The vital tasks of opinion mining is Mining opinion targets and words from the web reviews. The main aim is to notice opinion relations between words. During this paper, a novel Expectation Maximization (EM) is projected for opinion relations within the sort of alignment method. Subsequently graph-based co-ranking algorithm is studied. And at the last, a candidate who has higher con?dence is extracted. As compared with different strategies, this model is creating the task of opinion relations, for large-span relations additionally. As Compared with the syntax technique, the word alignment model is appearance for negative effects of when yearning for on-line texts. The experimental results show that this model obtains higher precision as Compared to the part supervised alignment model. Once projected system searches for candidate con?dence, it gets to understand that higher-degree vertices within the EM algorithm are decreasing the probability of the generation of error